Character of Spreading and Cytoskeleton Structure of Bone Marrow Mesenchymal Stem Cells Cultured on Chitosan Scaffolds - Kisil, A. V.; Kiroshka, V. V.; Bondarenko, T. P.; Petrova, V. A.; Baklagina, Yu. G.; Chernyakov, D. D.; Skorik, Yu. A. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):173.